2020
DOI: 10.1111/andr.12914
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant default mode network and auditory network underlying the sympathetic skin response of the penis (PSSR) of patients with premature ejaculation: A resting‐state fMRI study

Abstract: Introduction Hyperactivity of the sympathetic nervous system is considered as an important component involved in the pathological mechanisms of premature ejaculation (PE). However, the neural mechanisms of PE with high sympathetic activity are still not well understood. Methods The activity of the sympathetic innervations in the penis was evaluated by the sympathetic skin response of the penis (PSSR) with an electromyograph and evoked potential equipment. Resting‐state functional magnetic resonance imaging (fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Until now, only a few studies have explored the topological characteristics of the brain network in male sexual dysfunction using the method of graph theory ( Chen et al, 2018a , b , 2020c , 2021 ). With respect to PE, our previous studies found disrupted topological architectures in the white matter brain network of patients with primary PE and patients with depression ( Chen et al, 2020c , 2021 ), as well as functional abnormalities in those with high sympathetic activity ( Chen et al, 2020b ). In addition, brain functional biomarkers were identified for distinguish patients with PE from those with anejaculation by the method of resting-state functional magnetic resonance imaging (MRI) ( Chen et al, 2020e ).…”
Section: Introductionmentioning
confidence: 94%
“…Until now, only a few studies have explored the topological characteristics of the brain network in male sexual dysfunction using the method of graph theory ( Chen et al, 2018a , b , 2020c , 2021 ). With respect to PE, our previous studies found disrupted topological architectures in the white matter brain network of patients with primary PE and patients with depression ( Chen et al, 2020c , 2021 ), as well as functional abnormalities in those with high sympathetic activity ( Chen et al, 2020b ). In addition, brain functional biomarkers were identified for distinguish patients with PE from those with anejaculation by the method of resting-state functional magnetic resonance imaging (MRI) ( Chen et al, 2020e ).…”
Section: Introductionmentioning
confidence: 94%
“…All participants were instructed to relax, think of nothing in particular, stay awake with eyes closed, move as little as possible during the scan. Sagittal 3D T1-weighted images were acquired with the following parameters: repetition time (TR) =1900ms; echo time (TE)=2.48ms; flip angle (FA)=9°; field of view (FOV)=250mm×250mm; matrix size=256×256; slice thickness=1mm; number of slices=176 (42,43). Rs-MRI BOLD images were acquired with the following parameters: TR/ TE =3000/40ms; FA=90°; FOV=240mm×240mm; matrix size=64×64; slice thickness=4mm; number of slices=32; number of volumes=133 (42,43).…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
“…Sagittal 3D T1-weighted images were acquired with the following parameters: repetition time (TR) =1900ms; echo time (TE)=2.48ms; flip angle (FA)=9°; field of view (FOV)=250mm×250mm; matrix size=256×256; slice thickness=1mm; number of slices=176 (42,43). Rs-MRI BOLD images were acquired with the following parameters: TR/ TE =3000/40ms; FA=90°; FOV=240mm×240mm; matrix size=64×64; slice thickness=4mm; number of slices=32; number of volumes=133 (42,43). All subjects had no obvious structural damages examined by two radiologists based on conventional MRI images.…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that altered amplitude of low-frequency fluctuations (ALFF) of the frontal cortex, the parietal cortex, and the putamen might help distinguish premature ejaculation from anejaculation ( 5 ). Another study investigated the neural basis of patients with PE based on the measure of regional homogeneity (ReHo) ( 6 ). Patients with lifelong PE showed abnormal degree centrality (DC) value in the medial prefrontal cortex, the precuneus, the primary somatosensory cortex, and the orbitofrontal cortex ( 7 ).…”
Section: Introductionmentioning
confidence: 99%